Diversity of Molluscs (Gastropoda and Bivalve) associated with Mangrove species in Dondon Beach and Gerupuk Beach, Central Lombok - Insani, Reginah Fhathonah; Syukur, Abdul; Suyantri, Eni (Jurnal Biologi Tropis, 2024)
Mollusks are macrofauna found in mangrove environments. The aim of this research is to explain the association of mollusks with mangroves at Dondon Beach and Gerupuk Beach, Central Lombok. Furthermore, the research method uses transects and quadrants and determines transects using the purposive sampling method. Meanwhile, data analysis used descriptive statistics, the Shannon-Wienner diversity index, the Evenness uniformity index, the Simpson dominance index, and the Ludwig & Reynolds association index. Next, the relationship between mangroves and mollusks was analyzed using the Pearson correlation index. The results of this research found 2 mangrove species and 45 mollusk species at Dondon Beach, while 6 mangrove species and 21 mollusk species were found at Gerupuk Beach. Results of descriptive statistical analysis, Littorinidae was highest and Cardidae was lowest at Dondon Beach, Potamididae was highest and Muricidae was lowest at Gerupuk Beach. The mollusk species diversity index was the highest at station III Dondon Beach and 2.33 at station III Gerupuk Beach. The highest mollusk species uniformity index was 0.9 at station III Dondon Beach and 0.76 at station III Gerupuk Beach. The highest mollusk species dominance index was 0.12 at station II Dondon Beach and 0.16 at station II Gerupuk Beach. The relationship between mangroves and molluscs is based on Pearson correlation, at Dondon Beach, the r2 value = 0.9973 while at Gerupuk Beach, the r2 value = 0.2265. Mollusk and mangrove association types, 25 positive species and 17 negative species. Meanwhile, at Gerupuk Beach, 8 species had positive associations and 3 species had negative associations. The conclusion of this research is that the association between mollusks and mangroves is very strong at Dondon Beach and the correlation is weak at Gerupuk Beach.